A comprehensive optical analysis of nanoscale structures: from thin films to asymmetric nanocavities. Issue 37 (11th July 2019) - Lio, Giuseppe Emanuele; Palermo, Giovanna; Caputo, Roberto; De Luca, Antonio
Abstract : Hyper transmission of asymmetric nanocavity metamaterials; a comprehensive optical analysis of multi-layered nanostructures. Abstract : A simple and robust method able to evaluate and predict, with high accuracy, the optical properties of single and multi-layer nanostructures is presented. The method was implemented using a COMSOL Multiphysics simulation platform and it has been validated by four case studies with increasing numerical complexities: (i) a single thin layer (20 nm) of Ag deposited on a glass substrate; (ii) a metamaterial composed of five bi-layers of Ag/ITO (indium tin oxide), with a thickness of 20 nm each; (iii) a system based on a three-material unit cell (AZO/ITO/Ag), but without any thickness periodicity (AZO stands for Al2 O3 /zinc oxide); (iv) an asymmetric nanocavity (thin-ITO/Ag/thick-ITO/Ag). A thorough study of this latter configuration reveals peculiar metamaterial effects that can widen the actual scenario in nanophotonic applications. Numerical results have been compared with experimental data provided by real ellipsometric measurements performed on the above mentioned ad hoc fabricated nanostructures. The obtained agreement is excellent, suggesting this research as a valid design approach to realize multi-band metamaterials able to work in a broad spectral range.